The Role of Religiosity in Type 2 Diabetes Mellitus Patients: A Phenomenological Study - Abdullah AA; Adi Antoni; Anto J. Hadi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Diabetes Mellitus is part of a chronic disease that is prolonged and causes complications in other body organs which makes the sufferer have to live together for the rest of the sufferer's life which causes the sufferer to experience depression and boredom in his life. A person who has high religious values ??will be able to face everything patiently. Objective: This research aims to explore the expressions, experiences and feelings of Diabetes Mellitus sufferers in living their lives and interacting with the role of religiosity that every human being has.. Method: This research was conducted in Padangsidimpuan City. This type of qualitative research uses a phenomenological study design. The number of participants in this research was 7 participants. The method used in this research is Collaizzi. Result: The results of this research found 4 themes which explain the role of religiosity in type 2 diabetes mellitus sufferers. These themes are: 1) The role of religion as a source of strength and hope which consists of 2 sub-themes, namely (1) Religion as motivation, (2) Religion as strength. For Health, 2) Illness as a Trial and Strengthener of Faith which consists of 2 sub-themes, namely (1) Self-Acceptance of Illness, (2) Sickness Gets Closer to God, 3) Religious Practices Help Control Disease which consists of 2 sub-themes, namely ( 1) Worship makes you calmer (2) Worship makes life more meaningful, and 4) Make illness a friend, not an enemy, which consists of 2 sub-themes, namely (1) religion as a guide to activities (2) religion as self-control. Conclusion: This research can be used to increase insight for diabetes mellitus sufferers so that these patients can further increase their religiosity and this can also be applied by health workers to educate sufferers so they can increase their religiosity.